POLITICAL RELATIONS BETWEEN SERBIA AND MONTENEGRO-EVENTS AND OPPORTUNITIES SINCE 1896. Until 1903. (Heritage, 2020)
The period from 1896 to 1903 includes an interesting stage in Montenegrin-Serbian relations. The beginning of this period was reserved for the first direct meetings of the rulers of these two Serb states, and its end was marked by the change of the ruling dynasty in Serbia. In the aforementioned period, relations between the Kingdom of Serbia and the Principality of Montenegro have had their ups and downs. It can be said that in the period from 1896 to 1903 there were moments of the most cordial, and also moments of the most broken relationships, where the stumbling block was more the mutual animosity of Prince Nikola Petrovic and King Milan Obrenovic than that of King Alexander Obrenovic, who sat on the Serbian thronein the mentioned period. The struggle for all-Serb liberation and unification as the imperative of the two states would become both a field of necessary co-operation and rivalry, as both dynasties claimed the same non-liberated ethnic Serb territories. In this period, when the Obrenovic dynasty turned more to Austria, Montenegrin Prince Nikola saw an opportunity to win a stronger position in ''Serbian question'', with the support of Russia. A Particularly interesting fact isthat, despite the dynastic strife, the courts could put Serbian national interest in Old Serbia and Macedonia at the forefront.
Keywords: Serbia, Montenegro, Prince Nikola, King Alexander, King Milan, St. Vitus Day, Prizren, Old Serbia, Macedonia, Serbian Question